Financial and ethical risk-taking by young adults: A role for family dynamics during childhood - Shelia M. Kennison; Erin E. Wood; Jennifer Byrd-Craven; Megan L. Downing (Cogent Economics & Finance, 2016)
The research tested the hypothesis that childhood relationships with parents were related to risk-taking by young adults. Prior research has shown that risk-taking by young children is related to their interactions with mothers and fathers. Few studies have examined how family relationships during childhood are related to risk-taking by young adults. We assessed risk-taking using the domain-specific risk-taking scale (DOSPERT), which measures five domains of risk-taking: ethical, financial, health, recreational, and social. We also assessed sensation-seeking, a personality trait that has been shown to be a predictor of risk-taking and family dynamics, using a measure that quantifies positive and negative childhood relationships with each parent. The three key results were (1) negative mother interactions predicted men's financial risk-taking; (2) negative father interactions and disinhibition predicted men's ethical risk-taking; and (3) women's ethical risk-taking was predicted by negative father interactions, low positive mother interactions, and boredom susceptibility. Implications for identifying young adults most at-risk for ethical and financial risk-taking are discussed.
Keywords: 330; ethical risk-taking; financial risk-taking; young adults; family dynamics; sex differences